Nacionālo kvotu sistēmu pieaugošā ietekme uz sieviešu pārstāvību Eiropas Parlamentā. - Shin, Haemi (Latvijas Universitāte, 2019)
Eiropas Savienība ir daudzveidīga dalībvalstu grupa, un dzimumu līdztiesības attīstība kopš 1950. gada vēl nav pastāvīga un lineāra, kas savukārt ietekmē arī Eiropas Parlamenta dzimumu līdzsvaru. Pētījumā ir novērtēts sieviešu īpatsvars parlamentos, pamatojoties uz publiski pieejamiem datiem, ko apkopojuši galvenokārt Eurostat, Pasaules ekonomikas forums, Eiropas Dzimumu līdztiesības institūts un Starptautiskais demokrātijas un vēlēšanu palīdzības institūts. Pētījumā tika konstatēts, ka neatkarīgi no izmantotā dzimuma kvotu veida un īstenošanas perioda, dzimumu līdzsvara politikā bija dažādi rezultāti, tāpēc katrai valstij bija nepieciešama pielāgota pieeja.

The European Union is a diverse group of member states, and the progress and development of gender equality has not all been constant and linear since 1950. This study observes the specific effect of gender quotas to analyze whether it increases women’s representation in the national level and which in turn impact the gender balance of the European Parliament as well. The research measures the percentage of women in parliaments based on publicly available data compiled mainly by Eurostat, the World Economic Forum, the European Institute of Gender Equality, and the International Institute for Democracy and Electoral Assistance. The study established that regardless of the type of gender quota used and the period of implementation, the gender balance in politics had varying results, requiring a tailored approach for each country.
Growing Impact of National Quota Systems on Women's Representation in the European Parliament.
Keywords: Ekonomika; gender equality; comparative politics; feminist theory; representative democracy; European Union